Microleakage in mineral trioxide aggregate and biodentine as orthograde apical plugs in permanent teeth simulated with open apices: an in-vitro evaluation - Thapaliya, Bidhya; Koul, Monika Verma; Upadhyay, Vinod Kumar; Khare, Abhishek (Journal of Chitwan Medical College, 2021)
Background: The divergent apical architecture makes complete debridement and holding of the obturating material within the root canal impossible as no apical barrier exists, which may result in a canal that is susceptible to leakage. The aim of the study was to evaluate the apical microleakage of MTA AngelusR and BiodentineTM when used as orthograde apical plugs. Methods: Sixty extracted sound human anterior teeth simulated with open apices were equally distributed in two groups viz group A [MTA AngelusR (Mfd by Angelus, Brazil)] and group B [BiodentineTM (Mfd by Septodont, France)]. Apical microleakage in both groups was evaluated using dye penetration method. Dye penetration data of two independent groups were summarized as Mean ± SE (standard error of the mean) and compared by independent Student’s t test. A two-tailed (α=2) p<0.05 was considered statistically significant. Results: Apical microleakage of MTA AngelusR [Group A] ranged from 1.30 to 3.10 mm with mean (± SE) 2.16 ± 0.10 mm and median 2.05 mm whereas in BiodentineTM [Group B] it ranged from 0.20 to 1.20 mm with mean (± SE) 0.68 ± 0.06 mm and median 0.60 mm. Sealing ability of Group B (BiodentineTM) was significantly better (p<0.001) and 68.5% higher than Group A (MTA AngelusR). Conclusions: Both the materials exhibited microleakage. There was a significant difference ( P˂ 0.001) between the two groups and BiodentineTM showed to have less apical microleakage than MTA AngelusR.